1997
DOI: 10.1038/37776
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of adult axons in white matter tracts of the central nervous system

Abstract: It is widely accepted that the adult mammalian central nervous system (CNS) is unable to regenerate axons. In addition to physical or molecular barriers presented by glial scarring at the lesion site, it has been suggested that the normal myelinated CNS environment contains potent growth inhibitors or lacks growth-promoting molecules. Here we investigate whether adult CNS white matter can support long-distance regeneration of adult axons in the absence of glial scarring, by using a microtransplantation techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
500
7
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 699 publications
(537 citation statements)
references
References 28 publications
24
500
7
1
Order By: Relevance
“…14,48,[71][72][73][74]111 It has been demonstrated that reactive adult astrocytes upregulate the production of laminin and neurotrophin C. 75,76 In addition to the endogenously present myelinassociated neurite growth inhibitory constitutents, reactive astrocytes form an astroglial scar that acts as a physical and/or chemical barrier to axonal regeneration. 8,35,72,77,78 Proximity to the lesion epicentre determines whether the reactive glial environment will be growth supportive or inhibitory. 63 Although the functional role of glial scarring is not completely understood, it has been suggested to be an attempt by the CNS to restore homeostasis through isolation of the damaged region.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…14,48,[71][72][73][74]111 It has been demonstrated that reactive adult astrocytes upregulate the production of laminin and neurotrophin C. 75,76 In addition to the endogenously present myelinassociated neurite growth inhibitory constitutents, reactive astrocytes form an astroglial scar that acts as a physical and/or chemical barrier to axonal regeneration. 8,35,72,77,78 Proximity to the lesion epicentre determines whether the reactive glial environment will be growth supportive or inhibitory. 63 Although the functional role of glial scarring is not completely understood, it has been suggested to be an attempt by the CNS to restore homeostasis through isolation of the damaged region.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Chief of the many ECM molecules that serve to inhibit axonal regeneration are the chondroitin sulfate proteoglycans (CSPGs) (Eddleston and Mucke, 1993;Silver and Miller, 2004) that experience a great increase in expression following SCI (Lemons et al, 1999;McKeon et al, 1991). Both in vitro and in vivo studies have shown that axons do not extend into CSPG-rich ECM (Davies et al, 1997(Davies et al, , 1999McKeon et al, 1991;Meiners et al, 1995;Zuo et al, 1998), and specific CSPGs that inhibit neurite outgrowth have been identified including: aggrecan (Condic et al, 1999), neurocan , phosphocan , brevican (Yamada et al, 1997), versican (Schmalfeldt et al, 2000), and NG2 (Dou and Levine, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike axons in the peripheral nervous system, those in the CNS of adult mammals do not regenerate after injury (20,21). Failure to regenerate is attributed to a combination of axon growth arrest by myelin-associated and scar-derived inhibitor molecules (22,23), and to the absence of growth-promoting neurotrophic factors in the adult CNS (24).…”
mentioning
confidence: 99%